A Study of Move Analysis in American NPOs' Online Fundraising Pages: A Comparison between Domestic and Global Campaigns in Health Operations - Sakulthong, Nuttiya; Gampper, Chanika (LEARN Journal: Language Education and Acquisition Research Network, 2022)
This study examines the language used in the campaign descriptions (CDs) posted by nonprofit organizations (NPOs) through www.globalgiving.org, an international fundraising platform for nonprofits around the world. The purpose of this study aims to identify the similarities and differences among those that occurred in the campaign descriptions of domestic and global campaigns under the theme of health operations. One condition is that each NPO has to write a campaign description following the template provided by the website, which contains four different sections: ‘Summary’, ‘Challenge’, ‘Solutions’, and ‘Long-term Impact’. A move analysis on 158 CDs found six moves and 15 steps used across the descriptions in both corpora. The results suggested that ‘Identifying the Locations of the Problem’ was an essential move for the global campaigns, while this move was not necessary to be included in the domestic campaigns. The common rhetorical moves found in this study can help other NPOs that are planning on putting their campaigns online by writing their descriptions in English. The results will benefit nonprofits around the world. Language learners and professionals can also learn the persuasive writing style of fundraising discourses in this study.